Analisis Faktor – Faktor Yang Mempengaruhi Penyerapan Anggaran Belanja Pada Pemerintah Kota Cimahi - Rika Septi Rahmawati; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to determine the effect of budget planning, budget implementation, regulation, human resources, and procurement of goods and services to the absorption of the expenditure budget in Government of Cimahi. And to find out the obstacles that cause the absorption of the budget and how the solution are to overcome these obtacles. This research is a quantitative research. The data source used is primary data obtained through questionnaire and interviews. The questionnaires will be distributed to 27 Regional Apparatus Organization (OPD) in the Government of Cimahi. The analysis technique used is multiple linear regression analysis. The result of the research partially show that budget planning, budget implementation, regulation, and human resources have no effect on the absorption of the expenditure budget in the Government of Cimahi. Meanwhile simultaneously it shows that budget planning, budget implementation, regulation, human resources, and procurements of goods and services have a positive and significant effect on the absorption of the expenditure budget in the Government of Cimahi.